Limit theorems for twists of L-functions of elliptic curves. II - Garbaliauskienė, Virginija; Laurinčikas, Antanas (Mathematical Modelling and Analysis, 2012)
In the paper, a limit theorem for the argument of twisted with Dirichlet character L-functions of elliptic curves with an increasing modulus of the character is proved.